2019
DOI: 10.3390/jcm8101674
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Intraoperative Ferric Carboxymaltose in Joint Arthroplasty Patients: A Randomized Trial

Abstract: This study assessed the efficacy of intraoperative high-dose intravenous iron therapy in facilitating recovery from postoperative anemia and reducing the transfusion rate in patients with total knee and total hip arthroplasty. This prospective randomized controlled study involved 58 subjects. Group F received 1000 mg intravenous ferric carboxymaltose and Group C received normal saline. The changes in hemoglobin (Hb), hematocrit, iron metabolism variables, transfusion rates, and the arterial partial pressure of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(56 citation statements)
references
References 28 publications
2
54
0
Order By: Relevance
“…However, administration of preoperative IV iron is not always feasible, especially in emergency surgery. Infusing iron intraoperatively is more convenient, but data regarding the effectiveness of this approach are inadequate 19 . We thereby conducted a randomised controlled trial to evaluate the effects of intraoperative IV iron on postoperative Hb levels and transfusion requirements in patients undergoing bimaxillary orthognathic surgery.…”
mentioning
confidence: 99%
“…However, administration of preoperative IV iron is not always feasible, especially in emergency surgery. Infusing iron intraoperatively is more convenient, but data regarding the effectiveness of this approach are inadequate 19 . We thereby conducted a randomised controlled trial to evaluate the effects of intraoperative IV iron on postoperative Hb levels and transfusion requirements in patients undergoing bimaxillary orthognathic surgery.…”
mentioning
confidence: 99%
“…Among them, two RCTs reported that iron supplementation did not lower transfusion rates, but other five studies reported lowered transfusion rates when compared with those of the control group. Five studies were conducted in patients with anemia (hemoglobin 10 to 13 g/dL or 1-day post-operative hemoglobin < 10 g/dL) [ 25 , 26 , 30 32 ]. One study reported that hemoglobin was higher in the iron supplementation group when compared with that of the control group [ 25 ], and four studies reported that iron supplementation was effective in lowering the transfusion rate [ 25 , 30 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…Eleven articles were included in the final analysis. Seven randomized controlled trials (RCTs) [22][23][24][25][26][27][28], one prospective cohort study [29], and three retrospective cohort studies [30][31][32] were included for the final analysis. Two of them were studies with conflict of interest [23,32].…”
Section: Searchmentioning
confidence: 99%
See 2 more Smart Citations